2022
DOI: 10.3389/fonc.2022.799662
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging Biomarkers of Glioblastoma Treatment Response: A Systematic Review and Meta-Analysis of Recent Machine Learning Studies

Abstract: ObjectiveMonitoring biomarkers using machine learning (ML) may determine glioblastoma treatment response. We systematically reviewed quality and performance accuracy of recently published studies.MethodsFollowing Preferred Reporting Items for Systematic Reviews and Meta-Analysis: Diagnostic Test Accuracy, we extracted articles from MEDLINE, EMBASE and Cochrane Register between 09/2018–01/2021. Included study participants were adults with glioblastoma having undergone standard treatment (maximal resection, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…Many incorporate machine learning as a central pillar of the process. A review of studies up to 2018 ( 91 ), a systematic review of studies from 2018 – 2020 ( 122 ) using PRISMA-DTA methodology and a meta-analysis from 2018–2021 ( 123 ) indicated that those taking advantage of enhanced computational processing power to build monitoring biomarker models (e.g., using deep learning methods such as convolutional neural networks) have yet to show an advantage in performance compared with machine learning techniques using explicit feature engineering and less computationally expensive classifiers (e.g., using “classical” machine learning methods support vector machine). It is also notable that studies applying machine learning to build monitoring biomarker models have yet to show an overall advantage over those using traditional statistical methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many incorporate machine learning as a central pillar of the process. A review of studies up to 2018 ( 91 ), a systematic review of studies from 2018 – 2020 ( 122 ) using PRISMA-DTA methodology and a meta-analysis from 2018–2021 ( 123 ) indicated that those taking advantage of enhanced computational processing power to build monitoring biomarker models (e.g., using deep learning methods such as convolutional neural networks) have yet to show an advantage in performance compared with machine learning techniques using explicit feature engineering and less computationally expensive classifiers (e.g., using “classical” machine learning methods support vector machine). It is also notable that studies applying machine learning to build monitoring biomarker models have yet to show an overall advantage over those using traditional statistical methods.…”
Section: Resultsmentioning
confidence: 99%
“…It is also notable that studies applying machine learning to build monitoring biomarker models have yet to show an overall advantage over those using traditional statistical methods. There is good diagnostic performance of machine learning models that use MRI features to distinguish between progressive disease and diagnostic accuracy measures comprise recall = 0.61 – 1.00, specificity = 0.47 – 0.90, balanced accuracy = 0.54 – 0.83, precision = 0.58 – 0.88, F1 score = 0.59 – 0.94, and AUC = 0.65 – 0.85 ( 122 , 123 ). The recent meta-analysis of ten studies showed a pooled true positive rate (sensitivity) = 0.769 (0.649 – 0.858), a false positive rate (1-specificity) = 0.352 (0.251 – 0.468) and a summary AUC-ROC = 0.765.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first group consists of 13 studies that were published before 2018 (pre-2018), and the second group consists of 30 studies that were published in 2018 or later (post-2018). This arbitrary cut-off was chosen as it mirrors the notable observation that in 2018, arXiv (a repository where computer science papers are self-archived before publication in a peer reviewed journal) surpassed 100 new machine learning pre-prints per day 65 66. In the pre-2018 group, the lesion sensitivities ranged from 56.8% to 100% with false-positives/case ranging from 2.3 to 31.8.…”
Section: Resultsmentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) images derived from diffusion-weighted imaging have shown promise in highlighting areas of diffusion restricting hypercellularity associated with tumor, though recent studies validating this signature beyond the contrast-enhancing margin have disputed the strength of this relationship [14][15][16][17][18][19] . Machine learning approaches have also sought to maximize the amount of clinically relevant information we can extract from these non-invasive images, employing recent advances in computing to automatically segment the radiologist-defined margin, identify patient-level genetic signatures such as IDH1 mutation and MGMT methylation status, and predict cellular-level information using biopsy samples as validation [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%